On decomposability of countable systems of differential equations - Samoilenko, A. M.; Teplinsky, Yu. V. (Ukrains’kyi Matematychnyi Zhurnal, 1993)
Conditions under which there exists a change of variables that decomposes a countable system of differential equations are established for the entire real axis and a semiaxis. Similar problems are investigated for a countable system with pulse influence.